Implementasi Metode Extreme Programming untuk Pengembangan Sistem Inventory Sarana dan Prasarana pada Universitas Amikom Purwokerto - Praharaningtyas, Ranggi; Waluyo, Retno; Andika, Rizki; Hani, Nurul (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Universitas Amikom Purwokerto has not yet implemented a system for the procurement of facilities and assets, inventory, maintenance, supervision, and evaluation processes. All this time, we have been using a letter of request for goods from one division to another and carrying out other processes manually. Therefore, the process of item requisition and inventory requires the development of an inventory system. This research aims to develop a web-based inventory system using the CodeIgnite framework, while the system development method employs Extreme Programming (XP). The results of the research indicate that the use of the CodeIgnite framework and the Extreme Programming method can be utilized for the development of the inventory system at Universitas Amikom Purwokerto, which is used to manage the process of goods requisition and inventory. After conducting black box testing, it was concluded that all system features have been tested, and the results show that the system can operate according to the planning made during the planning stage.